Increased circulating Th17 cells and altered CD4 T cell maturation and differentiation in active tuberculosis with type 2 diabetes: a pilot study - Ogongo, Paul; Martinez-Lopez, Yoscelina E.; Tran, Anthony; Lindestam Arlehamn, Cecilia S.; Sette, Alessandro; Dominguez-Trejo, Ilse A.; Garza, Lizette; Cruz-Gonzalez, America M.; Loera-Salazar, Raul; Rodríguez-Herrera, Javier E.; Aguillón-Durán, Genesis P.; Garcia-Oropesa, Esperanza M.; et al. (Frontiers in Immunology, 2025)
IntroductionType 2 diabetes (T2D) is a major risk factor for developing tuberculosis (TB). However, understanding the role of defective T cell responses in T2D and TB has been difficult, largely due to inconsistencies across studies. These discrepancies often stem from T cell subset classification primarily relying on cytokine expression profiles, which may not fully capture the complexity of T cell maturation, differentiation, and function in TB patients with T2D.Objective and methodsIn this pilot study, we sought to identify alterations in phenotypic and ex vivo responses of CD4 T cells to Mycobacterium tuberculosis (Mtb) antigens in people with TB with or without T2D. We evaluated peripheral blood mononuclear cells (PBMC) by high-parameter spectral flow cytometry and assessed T cell differentiation using a cytokine agnostic approach based on validated cell surface markers expression.ResultsWe found major alterations in specific CD4 T cell properties by T2D status, despite no difference in the frequency of bulk CD4 or CD8 T cells. TB-T2D patients (vs TB alone) had fewer circulating naïve CD4 T cells, higher frequency CD4 T cell responses to Mtb antigens, and increased circulating Th1 and three subsets of Th17 cells. Multivariable analysis confirmed that T2D was independently associated with these alterations in maturation state, differentiation phenotype, and the activation of Mtb antigen-responsive CD4 T cells.ConclusionThis pilot study reveals CD4 T cell alterations in T2D that likely worsen TB outcomes. A reduced naïve CD4 T cell pool, increased central memory and antigen-activated CD4 T cells, and elevated Th1 and three Th17 cell subsets suggest a pro-inflammatory environment favoring responses that may promote, rather than control TB. These findings highlight immune dysfunctions that could be targeted by host-directed therapies to prevent TB and improve outcomes in T2D patients.